System-level design of a delta-sigma modulator target for next generation wireless application - Qiu, Xiaobo (2010)
Delta-sigma (Δ∑) converters have been widely used in wireless communications as they provide the most economic speed-accuracy tradeoff. This paper presents the system-level design of a multi-bit continuous-time (CT) Δ∑ analog-to-digital converter (ADC) targeting for the next generation wireless application. The modulator topology is determined based on the application requirements using MATLAB software. The nonidealities associated with the multi-bit CT Δ∑ modulator, such as excess loop delay, system clock jitter, integrator nonideality and multi-bit digital-toanalog converter (DAC) element mismatch, are also modeled in the system-level. With all the nonidealities included, the designed modulator achieves a dynamic range (DR) of 74dB (12 bits) in a 50-MHz signal bandwidth.